Target Attainment and Population Pharmacokinetics of Nirmatrelvir/Ritonavir in Critically Ill Adult Patients - Chen N; Yu X; Li L; Yang P; Dong R; Huang Y; Ling X; Shentu Q; Yu W; Jiang S (Infection and Drug Resistance, 2024)
Na Chen,1,2 Xuben Yu,3 Lu Li,1 Ping Yang,1 Rong Dong,1,4 Yizhen Huang,1,5 Xiao Ling,1,6 Qiaoqiao Shentu,1,7 Wenqiao Yu,8 Saiping Jiang1 1Department of Clinical Pharmaceutical, The First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2Zhejiang Provincial Key Laboratory for Drug Evaluation and Clinical Research, Hangzhou, People’s Republic of China; 3Department of Pharmacy, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People’s Republic of China; 4Department of Clinical Pharmacy, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 5Department of Pharmacy, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, People’s Republic of China; 6Department of Pharmacy, The People’s Hospital of Yuhuan, Taizhou, People’s Republic of China; 7Department of Pharmacy, Dongyang Red Cross Hospital, Jinhua, People’s Republic of China; 8Department of Hepatobiliary and Pancreatic Surgery and Intensive Care Unit, The First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, People’s Republic of ChinaCorrespondence: Saiping Jiang; Wenqiao Yu, Email j5145@zju.edu.cn; yuwenqiao1980@zju.edu.cnBackground: The population pharmacokinetics of nirmatrelvir/ritonavir (NIR/RIT) has not yet been described for critically ill adult patient.Purpose: This was a prospective observational population pharmacokinetic study of nirmatrelvir/ritonavir (NIR/RIT) in critically ill adult patients and identify optimal dosing regimens.Patients and Methods: The prescription of NIR/RIT is determined by the attending physician and ranges from 150mg/100mg to 300mg/100mg twice a day. Two to three serial blood samples were collected for each patient after the second doses. We developed and validated PK model for plasma NIR and plasma RIT. Monte Carlo dosing simulations were performed to assess target attainment.Results: We analyzed 89 plasma samples from 31 adult patients. The data were best described by a one-compartment model. Among the covariates tested on pharmacokinetic parameters, creatinine clearance (CrCL) and area under curve (AUC) of RIT had a significant effect on apparent clearance (CL/F) of NIR. Mean (SD) parameters estimates for the absorption rate constant (Ka), apparent distribution (V/F) and CL/F were 0.42 (0.10) h− 1. 36.5 (8.5) L, 3.6 (0.26) L/h, respectively. Dosing simulations showed that the target in vitro 90% effective concentration (EC90) was more likely to be achieved twice a day than once a day at the same daily dose of NIR. High CrCL, low AUC of RIT were associated with a reduced likelihood of NIR reaching the target EC90.Conclusion: Based on our dosing simulations, the initial dosage of NIR/RIT was 300mg/100mg twice a day in critically ill patients with CrCL> 45 mL/min; When CrCL in critically ill patients is between 15 and 45 mL/min, NIR/RIT is 150mg/100mg twice a day. The maintenance dose is adjusted according to CrCL and AUC of RIT, with the dosages varying between 75mg/100mg and 300mg/100mg.Keywords: nirmatrelvir, ritonavir, pharmacokinetics, critically ill, creatinine clearance